Technical efficiency of Jordanian banking sector based on DEA approach / Ammar Jreisat and Satya Paul - Jreisat, Ammar; Paul, Satya (2011)
This study examines efficiency levels of the Jordanian banking sector (13 domestic and 3 foreign banks) over the period 1996 to 2007, by estimating a non-parametric approach (Data Envelopment Analysis). The study also investigates the trends in estimated efficiency scores. Results indicate that large banks appear to be more efficient than small banks and domestic banks appear to be more efficient than foreign banks. Arab Bank is found to be the most technically efficient among large banks and Capital Bank of Jordan is found to be on average more technically efficient among all the medium banks also among the entire sample.